UPAYA MENINGKATKAN KEMAMPUAN BERPIDATO DENGAN MENGGUNAKAN METODE DEMONTRASI SISWA KELAS VI SD NEGERI 1 KUKUH KERAMBITAN TAHUN PELAJARAN 2009/2010 - Ni Made Sueni; I Wayan Nardi; Ni Kadek Ria Padmadewi (Jurnal Santiaji Pendidikan (JSP), 2011)
This study aims at obtaining the objective description about the improvement of speech ability using demonstration method of six grade students of SD Negeri 1 Kukuh Kerambitan in academic year 2009/2010. This study is classroom action research which consists of two cycles with 14 students. Each cycle consists of 4 stages : they are (1) planning, (2) action, (3) observation and evaluation, (4) reflection. Based on the data analysis, there was a significant improvement of speech ability of six grade students of SD Negeri 1 Kukuh Kerambitan. It is proved by the result of pretest with the average 55. 71 . After that, it was followed by the test on the cycle I with average 64.29, then increased to 76.43 on cycle II. As a result, the improvement from cycle I to cycle II is 12.14. Therefore, it can be suggested to the Indonesian language teachers to apply demonstration method in the learning process.